Estimasi Quantity Take Off dan Simulasi Progress Pekerjaan Struktur dengan Pendekatan Building Information Modeling: Estimation of Quantity Take Off and Simulation of Structural Work Progress with Building Information Modeling Approach - Sapitri; Subagja, Rusli; Annisa, Bismi (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2024)
Estimating the quantity of take-off and scheduling is crucial in a project life cycle. Errors in the calculation of quantity take-off and scheduling can result in the amount of budget costs incurred and the length of time of the development process. The development of Building Information Modeling (BIM) technology has provided benefits in solving problems faced by the construction industry. This study aims to calculate the Quantity Take-Off and find out the difference from the calculation of costs on building structural components (concrete and rebar volumes), as well as to make simulation for work progress. The BIM software used is Cubicost TAS (Take-off Architecture Structure) to create 3D modeling and Cubicost TRB (Take-off Reinforcement Bar) for Bar Bending Schedule (BBS) calculations. Meanwhile, scheduling simulation is conducted using Autodesk Naviswork. The results showed that the 3D BIM approach resulted in a smaller total concrete volume with a difference of 2.38% (lower 41.11 m3) than the conventional method. Similarly, for rebar material needs, it showed that the difference in rebar volume is 10.83% (30236.42 kg) smaller than conventional methods. The simulation results in 3D form show that using BIM Naviswork can help monitor the work progress between the design and the field according to the planned time based on the 3D model so that it looks more real-time.